DIGITAL MANUFACTURING BASED ON COMPUTER GRAPHICS IN UZBEKISTAN’S INDUSTRY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the evolution, current state, and future prospects of digital manufacturing based on computer graphics in Uzbekistan’s industry. By synthesizing academic literature, policy documents, case studies, and expert interviews, the study explores how 3D modeling, simulation, and visualization technologies are transforming industrial workflows, product development, and global competitiveness. Results indicate that digital manufacturing delivers significant benefits in productivity, cost efficiency, and innovation, particularly in automotive, machinery, and electronics sectors. However, challenges related to skills gaps, infrastructure investment, and regulatory adaptation persist. The article concludes by emphasizing the importance of continued government, industry, and academic collaboration to realize the full potential of computer graphics-based digital manufacturing in Uzbekistan.